Woman-centered Brazilian cinema : filmmakers and protagonists of the twenty-first century - Draper, Jack A., III, 1976-; Rêgo, Cacilda (State University of New York Press, 2022)
Illuminates the complex factors that have helped or hindered creative work by and about women in the twenty-first-century Brazilian film industry.
Description based upon print version of record.
Keywords: Women in the motion picture industry -- Brazil.; Women in motion pictures.; Motion pictures -- Brazil -- History.; Femmes dans l'industrie cinématographique -- Brésil.; Femmes au cinéma.; Cinéma -- Brésil -- Histoire.; History & Criticism.; Direction & Production.; Film & Video.; PERFORMING ARTS.; Screenwriting.; Women's Studies.; SOCIAL SCIENCE.; Motion pictures; Women in motion pictures; Women in the motion picture industry; Brazil; Electronic books.; History